2011
DOI: 10.4049/jimmunol.1002105
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the SLAM Family of Receptors Adapter EAT-2 as a Novel Strategy for Enhancing Beneficial Immune Responses to Vaccine Antigens

Abstract: Recent studies have shown that activation of the signaling lymphocytic activation molecule (SLAM) family of receptors plays an important role in several aspects of immune regulation. However, translation of this knowledge into a useful clinical application has not been undertaken. One important area where SLAM-mediated immune regulation may have keen importance is in the field of vaccinology. Because SLAM signaling plays such a critical role in the innate and adaptive immunity, we endeavored to develop a strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
68
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 54 publications
9
68
0
Order By: Relevance
“…5 A and B). Consistent with this association between EAT-2 expression and CD8 + T-cell responses, it was recently reported that adenoviral expression of EAT-2 as part of a vaccine strategy enhanced vaccine-induced T-cell responses (30). Because interaction network analysis of the overall CD8 + T-cell response gene set itself was found to be uninformative, we investigated whether any the gene set members are protein-protein interaction neighbors of genes belonging to MRKAd5 regulated functional modules (Fig.…”
Section: Preexisting Neutralizing Antibodies To Ad5 Attenuate the Innatementioning
confidence: 63%
See 1 more Smart Citation
“…5 A and B). Consistent with this association between EAT-2 expression and CD8 + T-cell responses, it was recently reported that adenoviral expression of EAT-2 as part of a vaccine strategy enhanced vaccine-induced T-cell responses (30). Because interaction network analysis of the overall CD8 + T-cell response gene set itself was found to be uninformative, we investigated whether any the gene set members are protein-protein interaction neighbors of genes belonging to MRKAd5 regulated functional modules (Fig.…”
Section: Preexisting Neutralizing Antibodies To Ad5 Attenuate the Innatementioning
confidence: 63%
“…One compelling component of the gene signature was EAT-2 ( Fig. 5B), which was recently reported to enhance the frequency of vaccine induced T cells when encoded in an Ad5 vector (30). Despite the striking differences in innate response kinetics between the vaccines, we also tested whether the CD8 + signature for MRKAd5/HIV was associated with CD8 + T-cell response magnitudes for YF-17D.…”
Section: Discussionmentioning
confidence: 99%
“…Because EAT-2 is the only known SLAM-associated adaptor protein expressed in DCs and macrophages, it has been proposed that EAT-2 facilitates SLAM-dependent immunoregulatory function (such as proinflammatory cytokine expression) in these cell types (22). Based on these facts, we demonstrated that expression of EAT-2 from a vaccine platform triggers early activation of innate immune cells in vivo and consequently improved the induction of Ag-specific adaptive immune responses (19,20). Specifically, Ad vaccine-mediated EAT-2 expression improved elaboration of beneficial cytokine and chemokine responses, enhanced the early activation of NK and NKT cells, and improved APC function by upregulating the expression of maturation markers, including CD40, CD80, CD86, MHC class II, and CCR7 (19).…”
mentioning
confidence: 91%
“…Specifically, Ad vaccine-mediated EAT-2 expression improved elaboration of beneficial cytokine and chemokine responses, enhanced the early activation of NK and NKT cells, and improved APC function by upregulating the expression of maturation markers, including CD40, CD80, CD86, MHC class II, and CCR7 (19). Improvements in innate immune system recruitment correlated with induction of superior cytolytic CD8 + T cell-mediated immune responses to several Ags, including HIV-1/Gag (19) and the malaria circumsporozoite protein (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation